Hyperbolically Bi-Lipschitz Continuity for -Harmonic Quasiconformal Mappings - Xingdi Chen (International Journal of Mathematics and Mathematical Sciences, 2012)
We study the class of -harmonic -quasiconformal mappings with angular ranges. After building a differential equation for the hyperbolic metric of an angular range, we obtain the sharp bounds of their hyperbolically partial derivatives, determined by the quasiconformal constant . As an application we get their hyperbolically bi-Lipschitz continuity and their sharp hyperbolically bi-Lipschitz coefficients.